Menguji Kembali Pemikiran Yusuf Al-Qardawi dalam Penentuan Awal Bulan Hijriah - ABDUL MUFID (Nuansa : Jurnal Studi Islam dan Kemasyarakatan, 2020)
This study explores and criticizes the views of Yusuf al-Qardhawi in determining the beginning of the Islamic month. Based on several valid hadiths, Yusuf al-Qaradawi is of the view that the determination of the beginning of the Hijri month can be carried out by three methods, namely rukyat (observation), hisab (astronomical calculations), and istikmal. Therefore, the fundamental question that will be examined in this paper is how is Yusuf al-Qaradawi's view when clarified by the study of hadith and astronomical studies? The main source for Muslims in understanding Islamic teachings is the Koran and Hadith. For Muslims, the Hadith second ranks after the Koran. Throughout Islamic history, hadith is a source of controversy in Islamic law. Among the problems that are still warm and almost always occur today is an understanding of the observations of the crescent related to the determination of the beginning of the Islamic month. Questioning about the differences in determining the beginning of the Hijri month is the result of different perspectives to understand the hadith about crescent observations. Therefore, the method of understanding the hadith about "crescent observation" is very urgent to be investigated more deeply. The final conclusion of this literature-based research process can be seen that the impact of Yusuf al-Qaradawi's understanding of the crescent observation traditions is al-Qaradawi's hope to unite fasting and Eid al-Fitr in Europe on the basis of priorities, not unifying all Muslims in the hemisphere of the earth.